Analyzing human balance recovery action using calculated torques of a double pendulum model. (2019) - Petró, Bálint; Kiss, Bernadett; Kiss, Rita M
Abstract: Assessment of balancing abilities require quantification of balancing motion response, typically using a kinematic or dynamic model of the human body. In this proof of concept work, we demonstrate a 4 degrees-of-freedom, two-link double pendulum model of the human body created according to the Denavit-Hartenberg convention and its utility in a sudden perturbation balance test. The model is used to calculate the estimated forward and sideways torques at the ankle and hip level based on measured position data from a motion capture system. From the joint torques, the total mechanical work of each joint can be obtained. Eleven healthy, young participants (9M/2F; age: 22.8±1.7 yrs, height: 179±11 cm, body mass: 80.6±19.9 kg) were studied to obtain the motion capture data in bipedal and unipedal stance. The model shows an estimation of the proportional contribution of the major joints to the balance response motion. A simple joint strategy index, defined as the proportion of ankle contributions can indicate the use of an ankle or a mixed ankle-hip joint strategy in the different stances. Using ratio-like variables, the model was able to detect a correlation between the joint works applied in the different directions and the corresponding platform motion. Overall, the model allows to further analyze and better understand balance maintenance and the complex balance recovery action. In the future, the model could be evaluated for different types of balancing tests used in clinical practice